Polyurethane/graphene oxide nanocomposite and its modified asphalt binder: Preparation, properties and molecular dynamics simulation. (1st November 2021) - Yu, Ruien; Wang, Qian; Wang, Wei; Xiao, Yue; Wang, Zhiyu; Zhou, Xing; Zhang, Xiaoyan; Zhu, Xijing; Fang, Changqing
Graphical abstract: Highlights: The prepared PU/GO composite modified asphalt was uniformly dispersed. Synergy effect of polymer and nano-modification improved the performance of asphalt. Molecular simulation and experiment completely revealed mechanism of modified asphalt. Abstract: In this paper, reactive polyurethane and graphene oxide were used to prepare polyurethane/graphene oxide (PU/GO) nanocomposite, which were polymerized in situ and then were sheared at high-speed in asphalt. The uniform dispersion of nanocomposite modified asphalt system with PU and GO was obtained. The macroscopic properties and microscopic changes of modified asphalt binders were studied from the aspects of mechanics, physical structure and composition. The relationship between the structure and properties of modified asphalt system was discussed. The molecular models of base asphalt, polyurethane modified asphalt and PU/GO nanocomposite modified asphalt were built in Materials Studio, which were simulated by molecular dynamics. The structural changes under the interaction of each molecule were analyzed. The solubility parameters, mean square displacement, radial distribution function, radius of gyration and glass transition temperature of these models were calculated. The results show that GO is well dispersed in PU and polymer particles are more uniform. The polymer particles with GO achieve good dispersion in the asphalt system. Synergy effect of polymer and nano modification was realized in the dispersed modified asphalt material and properties were improved.